2019
DOI: 10.1111/bph.14777
|View full text |Cite
|
Sign up to set email alerts
|

Ibudilast attenuates doxorubicin‐induced cytotoxicity by suppressing formation of TRPC3 channel and NADPH oxidase 2 protein complexes

Abstract: Background and Purpose Doxorubicin is a highly effective anticancer agent but eventually induces cardiotoxicity associated with increased production of ROS. We previously reported that a pathological protein interaction between TRPC3 channels and NADPH oxidase 2 (Nox2) contributed to doxorubicin‐induced cardiac atrophy in mice. Here we have investigated the effects of ibudilast, a drug already approved for clinical use and known to block doxorubicin‐induced cytotoxicity, on the TRPC3‐Nox2 complex. We specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 61 publications
0
16
1
Order By: Relevance
“…As to the possibility of the improvement of severe COVID-19 by clomipramine, we suggest an anti-inflammatory effect of clomipramine like ibudilast 17 . We have previously reported that transient receptor potential canonical (TRPC) 3 protein, a major component of receptor-activated cation channels, contributes to pathological myocardial atrophy caused by anti-cancer drug treatment 16 , by promoting NADPH oxidase (Nox) 2dependent reactive oxygen species (ROS) production on cardiac plasma membrane through interacting with Nox2 and preventing Nox2 from ER-associated degradation 20 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As to the possibility of the improvement of severe COVID-19 by clomipramine, we suggest an anti-inflammatory effect of clomipramine like ibudilast 17 . We have previously reported that transient receptor potential canonical (TRPC) 3 protein, a major component of receptor-activated cation channels, contributes to pathological myocardial atrophy caused by anti-cancer drug treatment 16 , by promoting NADPH oxidase (Nox) 2dependent reactive oxygen species (ROS) production on cardiac plasma membrane through interacting with Nox2 and preventing Nox2 from ER-associated degradation 20 .…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we focused on ACE2 internalization as a therapeutic target of severe COVID-19. Among 13 approved drugs that we have previously identified as potent inhibitor of cardiotoxicity caused by doxorubicin treatment 16,17 , clomipramine, a tricyclic antidepressant 18 , was found to suppress SARS-CoV-2 invasion and infection in TMPRSS2-expressing VeroE6 cells and human iPS-derived cardiomyocytes (iPS-CMs). Clomipramine also synergistically suppresses SARS-CoV-2 virus infection with remdesivir, suggesting the potential as a breakthrough treatment for severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… 90 We recently screened a potent inhibitor of the TRPC3-Nox2 complex using a library of already approved drugs and found that ibudilast, a PDE4 inhibitor approved for the treatment of asthma and dizziness secondary to chronic cerebral circulation impairment associated with the sequelae of cerebral infarction, significantly suppressed doxorubicin-induced atrophic shrinkage of cardiomyocytes and skeletal muscles, as well as macrophage cell death. 97 98 However, our preliminary experiments indicate that TRPC3 selective inhibitors have little impact on VSMC plasticity or vascular diseases, including peripheral arterial disease. This may be because TRPC6 is highly expressed in VSMCs and predominantly regulates VSMC plasticity, rather than the TRPC3 channel or the TRPC3-Nox2 protein complex.…”
Section: Therapeutic Potential Of Trpc Channels In Cardiovascular Dismentioning
confidence: 84%
“…Dox is a well-established anticancer drug, but it broad-spectrum cytotoxicity has also been reported (Nishiyama et al, 2019). Using Dox as a cellular toxicity positive control, we determined each of the chemical synthetic drugs in NLTC for the mechanistic insights, such as mitochondrial mass, mitochondrial membrane potential, and intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%